Analisis Pelaksanaan Program Sanitasi Berbasis Masyarakat terhadap Pemberdayaan Masyarakat di Kelurahan Bajak Kecamatan Teluk Segara Kota Bengkulu - Azuwandri Azuwandri (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the level of empowerment, socio-cultural success, and the success of community-based sanitation programs using descriptive research that provides a detailed description of a particular situation, structure or social relationship. The analytical method used is the Likert scale, the Likert scale is used to measure the description and analysis of the implementation of the community-based sanitation program, then the reliability test is carried out. The results of the research using a questionnaire in the Likert Scale calculation, the interpretation of the score is in the number 81% to 100%, the percentage listed is very strong. Based on the results of the study using the validity test with a value of rcount (Corrected Item-Total Correlation)> rtabel of 0.2272, it is thus said to be valid, while the reliability test obtained a success rate of 0.824, socio-culture of 0.742, and a program success rate of 0.793 which means the three variables declared reliable or meet the requirements. This, the success rate of implementing the community-based sanitation program with this program has been carried out efficiently and has actually activated community participation in its implementation.